TRANSFORMATION PROCESSES OF THE MAHALLA INSTITUTION IN THE DEVELOPMENT OF CIVIL SOCIETY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the significance and transformation of the mahalla institution in Uzbekistan's civil society development. Historically rooted in cultural traditions, the mahalla serves as a national form of self-governance, actively participating in social, moral, and economic processes. The study analyzes the mahalla's roles in youth education, public oversight, social cohesion, and citizen participation in governance. Additionally, it explores practical aspects of Anglo-Saxon and European models to enhance the mahalla system's effectiveness. ([Uzbek Embassy][1], [LinkedIn][2])